A method of failure identification and diagnostics for use with the systems for adaptive control through the application of the functions of Walsh - Andonov, Antonio (Journal scientific and applied research, 2012)
The ever increasing interest in the adaptive control, especially in the various aspects of identifi-cation and estimation of the subjects of the control is a natural reaction to two existing tendencies in the evolution of the systems for adaptive control. The first of these tendencies is connected with the increasing requirements concerning the higher quality of the control systems, which reflects on the requirements placed on the modeling of the plants of the control used in the synthesis of the systems in question. The second tendency is connected with the considerable progress made in the computer technique and the actual possibilities of its use in the solution of complicated problems in the failure identification and diagnostics. The approach suggested, based on the use of the functions of Walsh is the most effective means for analysis because the practicable application of the Wiener's theory to the non-linear systems considered.